2013
DOI: 10.1039/c3dt51130h
|View full text |Cite
|
Sign up to set email alerts
|

The chain-like polynuclear coordination compounds (ZnBr2)n(18-crown-6)2 (n = 4, 6, 8, 10) and [Zn5Br9][N(Tf2)]

Abstract: The chain-like polynuclear coordination compounds (ZnBr2)n(18-crown-6)2 (n = 4, 6, 8, 10) and [Zn5Br9][N(Tf)2] are obtained by reacting ZnBr2, SnBr4 and 18-crown-6 in the ionic liquid [(n-Bu)3MeN][N(Tf)2] (N(Tf)2: bis(trifluoromethylsulfonyl)imide). Structurally, chain-like anionic building units with corner- and edge-sharing ZnBr4/Zn(Br,O)4 tetrahedra of increasing lengths are obtained for (ZnBr2)n(18-crown-6)2. In contrast, [Zn5Br9][N(Tf)2] exhibits a cationic [Zn5Br9(18-crown-6)2](+) building unit with dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…Surprisingly, controlled Br 2 ‐release was observed from Zn 6 Br 12 (18‐crown‐6) 2 · (Br 2 ) 5 to Zn 4 Br 8 (18‐crown‐6) 2 · (Br 2 ) 3 and Zn 6 Br 12 (18‐crown‐6) 2 · (Br 2 ) 2 via crystal‐to‐crystal transformation with retention of the crystal shape (Figure b). In all reactions, the ionic liquid turned out as essential due to its weakly‐coordinating properties, its chemical stability, and due to the reduction of the vapour pressure of elemental bromine , , . Moreover, we observed that the presence of Lewis acids such as SnBr 4 is prerequisite for Br – subtraction from ZnBr 2 as the starting material , …”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Surprisingly, controlled Br 2 ‐release was observed from Zn 6 Br 12 (18‐crown‐6) 2 · (Br 2 ) 5 to Zn 4 Br 8 (18‐crown‐6) 2 · (Br 2 ) 3 and Zn 6 Br 12 (18‐crown‐6) 2 · (Br 2 ) 2 via crystal‐to‐crystal transformation with retention of the crystal shape (Figure b). In all reactions, the ionic liquid turned out as essential due to its weakly‐coordinating properties, its chemical stability, and due to the reduction of the vapour pressure of elemental bromine , , . Moreover, we observed that the presence of Lewis acids such as SnBr 4 is prerequisite for Br – subtraction from ZnBr 2 as the starting material , …”
Section: Resultsmentioning
confidence: 80%
“…In the system ZnBr 2 /Br 2 /(18‐crown‐6), we could identify a great number of coordination compounds (ZnBr 2 ) n (18‐crown‐6) 2 ( n = 4,6,8,10) that contain chain‐like anionic building units with corner‐ and edge‐sharing ZnBr 4 /Zn(Br,O) 4 tetrahedra of increasing lengths . Hereof, the hexanuclear ZnBr 4 tetrahedra chain in Zn 10 Br 20 (18‐crown‐6) 2 represents one of the largest discrete polynuclear metal‐halide chains described untill now (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have frequently observed such effect related to the presence of strong Lewis acids such as SiBr 4 , SnBr 4 , or SnI 4 . [9,15] Although the respective species remain in solution subsequent to the reaction, the abstraction of Brby SiBr 4 and the resulting influence on the total stoichiometry -especially on the Br --to-Br 0 ratio of the reaction -can be rationalized as highly relevant. According to structure analysis based on single crystals, both title compounds crystallize in the monoclinic space group C2/c and exhibit very similar cell parameters ( Table 1) The [Pt 2 Br 10 ] 2anion is composed of two edge sharing PtBr 6 octahedra with Pt-Br distances ranging between 243.0(1) and 251.3(1) pm in 1 and 243.0(2) and 250.3(1) pm in 2 ( (Table 2).…”
Section: Resultsmentioning
confidence: 99%